The Influence of Competence, Motivation, Self-Efficacy and Compensation on Job Satisfaction and Employee Performance: Human Resource Management - Rita Mulyanti (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This research aims to examine the influence of competence, motivation, self-efficacy, and fulfillment on employee performance which is mediated by job satisfaction. The research method uses a literature review study. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The findings of this research are as follows: 1) competence influences employee performance; 2) motivation influences employee performance; and 3) self-efficacy influences employee performance; 4) compensation affects employee performance; 5) job satisfaction influences employee performance.